2013
DOI: 10.1097/dcr.0b013e3182760506
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Short- and Medium-term Outcomes Comparing Emergent Surgery and Stenting as a Bridge to Surgery in Patients With Acute Malignant Colonic Obstruction

Abstract: Despite a high rate of technical and clinical success in selected patients with colonic obstruction, stenting has no impact on stoma rates. Despite concerns about the rate of stent-associated perforation, stenting does not adversely impact disease progression or survival. Future comparative trials are essential to better define the role of stenting in this setting and to ensure that we are not using costly technology to create an elective operative situation without concomitant patient benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 23 publications
3
19
1
Order By: Relevance
“…This contradicts other studies that conclude that stenting is a cost-effective procedure with reduced hospital stay and lower costs compared to ES. [34][35][36] If we focus on oncology outcomes, we do not see significant differences in LR rate, DFS or CSS in either group. This may be due to the small patient number in the study.…”
Section: Discussionmentioning
confidence: 77%
“…This contradicts other studies that conclude that stenting is a cost-effective procedure with reduced hospital stay and lower costs compared to ES. [34][35][36] If we focus on oncology outcomes, we do not see significant differences in LR rate, DFS or CSS in either group. This may be due to the small patient number in the study.…”
Section: Discussionmentioning
confidence: 77%
“…With the progression of disease, the septic patients prone to develop multiple organ dysfunction, and resulting in prolonged the hospital stay and increased hospital mortality [13]. Most of patients with CRC obstruction have poor overall physical health and longer time Obstruction Induced Sepsis potential development [9]. Once these patients complicated with sepsis, the selection of surgical procedures is crucial for the short-and long-term outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, many studies have showed that SEMS placement followed by elective operation represents a relatively safe and simple alternative to conventional emergency surgery (ES) [7][8][9][10]. SEMS placement during pre-operation can prevent high-risk morbidity, decrease stoma creation and increase primary anastomosis [9].…”
Section: Introductionmentioning
confidence: 99%
“…In the ES group there were 1 local/liver, 2 peritoneal, and 3 liver; the local recurrence occurred in a single patient who had a R1 resection. Kavanagh reported the histological evidence of clinically silent tumor micro perforations in 3 patients in the CS group (13%) in comparison with 2 (7%) tumor micro perforations in the ES group and this suggested that it is occasionally present in the absence of stent deployment [35] . Gorissen reported that SEMS was associated with an increased local recurrence rate in the younger patients aged 75 years or less.…”
Section: Risk Of Perforation After Sems Insertionmentioning
confidence: 99%
“…Data showed no difference in cancer specific and all cause mortality between both groups; there were 3 cancer related deaths in the CS group and 4 in ES group. Median follow up (months) in CS and ES group was 27.4 (range 1-81) and 26 [35] . Disease recurrence occurred in 4 patients in the CS group and 6 patients in the ES group; sites of recurrence in the CS were: local/peritoneal in two patients, liver in two patients; both local recurrences occurred in patients who had undergone R1 resections.…”
Section: Risk Of Perforation After Sems Insertionmentioning
confidence: 99%